Antioxidant-Spotting in Micelles and Emulsions - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C; Pastenes, C (Elsevier Ltd, 2018)
A simple protocol is described for locating the site of action of an antioxidant (AO) in a micro-heterogeneous mixture, based on the pattern of the reactivity curve towards the AO of a series of 4-alkanoyl TEMPO radicals. The resulting cut-off curves yield information regarding the hydrophobic microenvironment surrounding the reactive AO group, and its accessibility by the probe. Convex curves are an indication of an AO located in a more hydrophilic environment, while concave plots originate from AOs in a more hydrophobic location in the micro-heterogeneous system. © 2017 Elsevier Ltd